Role of Diffusion-Weighted Imaging and Apparent Diffusion Coefficient in Differentiating Between Local Tumor Recurrence and Benign Breast Changes after Breast Conservative Surgery (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: diffusion-weighted imaging; apparent diffusion coefficient; breast lesions